Perempuan Korban Tindak Pidana Kekerasan dalam Rumah Tanggapada Masa Pandemi Covid-19 - Ida Ayu Viony Adniasari; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Preferensi Hukum, 2022)
Domestic Violence is a very serious threat for women because not only is the number of cases of violence experienced increasing, but the increase is also increasingly worrying. The number of female victims who experience domestic violence continues to increase every year, especially during the time the coronavirus spreads. The purpose of this study is to discuss the factors that cause women to become victims of criminal acts of domestic violence during the Covid-19 pandemic and to analyze countermeasures that can be taken to prevent women from becoming victims of criminal acts of domestic violence during the Covid-19 pandemic. -19. In conducting research, empirical law is used through criminological techniques used in research. Sources of legal materials consist of primary and secondary materials. The technique in collecting legal materials with data collection is by quoting, letting go, and providing proposals for legal materials than in the data in a loose note by recording the name of the author, book title, publisher name, publisher year, and page number quoted. The conclusions from the results of this study are the factors that women become victims of criminal acts of domestic violence include personality characteristics, past trauma, narcotics abuse, economic problems and the social environment. Countermeasures in the context of preventing women from becoming victims of criminal acts of domestic violence can be carried out in a preventive and repressive manner.